The plant love kitchen : an easy guide to plant-forward eating, with 75+ recipes - Moore, Marisa (Washington, D.C. : National Geographic, 2023)
"Marisa Moore, R.D., offers a flexible approach to a more plant-forward diet that can improve your health"-- Provided by publisher
Includes index
Includes bibliographical references
Primary
Keywords: Vegetarian cooking; Vegetarian cooking -- Nutrition; Vegan cooking; Vegan cooking -- Nutrition; Cooking (Natural foods)